EFFECT OF POLYMER (S.B.R.)ON SULFATE RESISTANCE OF CONCRETE - M. Mohammed, Aseel; A. S. Al-Jumaily, Ibrahim (Iraqi Journal of Civil Engineering, 2007)
ABSTRACT:The resistance of concrete to sulfate attack is considered as one of the important factors for concrete durability.The effect of SBR polymer on sulfate resistance of concrete is investigated. Both internal and external sulfate attack are considered.Internal sulfate attack was made by adding gypsum to raise the sulfate content of sand to that of Ramadi city soil (2.17%), while the external sulfate attack was made by adding chemical materials (MgSO4.7H2O, Na2SO4, CaCl2.2H2O, NaCl) to tap water to convert it into water similar to groundwater of Ramadi city.The laboratory tests were compressive and flexural strength, modulus of elasticity, slump, ultra-sound velocity and total percentage of sulfate after exposing to attack for different ages. It was found that the compressive strength of reinforced normal concrete (RNC) for ages (7,28,90,180) days respectively were (20,28,11.166,7) MPa, the compressive strength of polymer Portland cement concrete( PPCC) with polymer/cement ratio( P/C)=5% (PPCC5) were (21.83,32.666,12.766,8.733) MPa and for PPCC with (P/C)=10% were (24.166,35.866,15.533,11.366)MPa.While the flexural strength of RNC for different ages (7,28,90,180) respectively were (3.953,3.7,1.68,11.305) MPa, the flexural strength of PPCC5 were (4.05,5.025,2.13,1.605) MPa and for PPCC10 were (4.43,6.375,2.43,1.92) MPa.The static modulus of elasticity at age (28) days for (RNC) was (37.4) GPa , for PPCC5 was (9.7) GPa and for PPCC10 was (13.63) GPa.Slump for (RNC) was (155) mm, for PPCC5 was (142) mm and for PPCC10 was (75) mm.T he ultra-sound velocity of RNC for ages (7,28,90,180) respectively were (4.2,4.445,4.203,4.53) Km/sec , for PPCC5 were (4.36,4.646,4.53,4.176) Km/sec and for PPCC10 were (4.437,4.837,4.656,4.52) Km/sec.It was found that (PPCC10) has higher resistance to sulfate attack than (PPCC5) and (NRC). The thesis refers to necessity of polymer to improve the resistance of concrete to sulfate attack although if the sulfate percentage raise to more than (0.5) % which represents the maximum limit of sulfate percentage in I.O.S No. 45-1970.